APLIKASI PEMETAAN DAERAH RAWAN GIZI DAN STATUS GIZI BAYI DAN BALITA DI SEMARANG MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (sig) - Ratih Sari Wardani; Rahayu Astuti (Universitas Muhammadiyah Semarang, 2008)
Mapping application of a vulnerable area of nutrition and Nutritional Status of Infants and Balita in Semarang using Geographic Information System Background Geographic Information System (GIS) is a potential as information systems more effective in the management of health programs because GIS has the ability to process database and display both spatial information (image maps) and non-spatial information in the forms of writing or numbers. Given the magnitude of nutrition problems in the community needed a system for recording and reporting reliable. The system will help of health workers to analyze data on the situation place/area and specific time so that decision-making will be more rapid, precise and accurate. Objective to design and create mapping application of a vulnerable area of nutrition and nutritional status ofiInfants and balita in Semarang by using GIS Methode types of this research is descriptive qualitative research with waterfall approach (system engineering, analysis, design, programming and testing) for its design. Object under study is a process the information on seksi gizi Subdin Kesehatan Keluarga. Research subject are seksi gizi Subdin Kesehatan keluarga staffs. The collection of data through observation, interview and literature study and analyzed the data descriptively. Result The research is the system specification to be developed, which is modeled in the context diagram and data flow diagram to obtain the data base, design inputs, outputs and interfaces. The design was changed to a program using the programming language and performed manual is digitation digital maps and tested the resulting application use. Conclusion 1). Getting a database consisting of files balita, district and village 2) Getting a draft mapping of vulnerable areas of nutrition and nutritional status of infants and balita based on the Semarang city.3 mapping application getting a vulnerable area of nutrition and nutritional status of infants and balita based GIS in the Semarang City. Keyword Nutrition Status, vulnerable area of nutrition, Geographic Information System